Paramonodictys phellodendri sp. nov., associated with medicinal plant Phellodendron amurense in Guizhou, China - Zou, Shi-Ping; Shi, Chang-Li; Yu, You-Yuan; Lu, Yong-Zhong; Liu, Ning-Guo; Xiao, Yuan-Pin; Cheewangkoon, Ratchadawan (Phytotaxa, 2025)
Paramonodictys (Parabambusicolaceae, Pleosporales) species have been reported from both freshwater and terrestrial habitats in China and Thailand, colonizing various host plants. The genus is characterized by its asexual morph, which has present or absent stroma and globose to subglobose, brown, muriform conidia. In this study, two terrestrial isolates were obtained from decaying branches of Phellodendron amurense (Rutaceae, Angiospermae) in Guizhou Province, China. Morphological comparisons and multi-gene phylogenetic analyses based on a combined dataset of LSU, ITS, SSU, and tef1-α sequences revealed that these two isolates are conspecific and distinct from other Paramonodictys species. Consequently, Paramonodictys phellodendri sp. nov. is introduced with a detailed description and illustration. Additionally, a synopsis of accepted Paramonodictys species is also provided.